2018
DOI: 10.1172/jci120518
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 7 sustains DNA damage response and promotes cervical carcinogenesis

Abstract: Central to the recognition, signaling, and repair of DNA double-strand breaks (DSBs) are the MRE11-RAD50-NBS1 (MRN) complex and mediator of DNA damage checkpoint protein 1 (MDC1), the interplay of which is essential for initiation and amplification of the DNA damage response (DDR). The intrinsic rule governing the regulation of the function of this molecular machinery remains to be investigated. We report here that the ubiquitin-specific protease USP7 was physically associated with the MRN-MDC1 complex and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 83 publications
3
77
0
Order By: Relevance
“…Ubiquitin-specific protease 7 (USP7), also named as herpesvirus-associated ubiquitin-specific protease (HAUSP) is one of the most investigated DUBs and has been associated with the initiation and progression of various cancers (Masuya et al, 2006;Su et al, 2018). USP7 has a broad range of substrates, such as the tumor suppressors p53 and PTEN (Phosphatase and tensin homolog) (Song et al, 2008) and the transcription factor FOXO4 (Forkhead box protein O4) (van der Horst et al, 2006), most of which are related to tumor suppression, DNA repair, and immune response (Pozhidaeva and Bezsonova, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin-specific protease 7 (USP7), also named as herpesvirus-associated ubiquitin-specific protease (HAUSP) is one of the most investigated DUBs and has been associated with the initiation and progression of various cancers (Masuya et al, 2006;Su et al, 2018). USP7 has a broad range of substrates, such as the tumor suppressors p53 and PTEN (Phosphatase and tensin homolog) (Song et al, 2008) and the transcription factor FOXO4 (Forkhead box protein O4) (van der Horst et al, 2006), most of which are related to tumor suppression, DNA repair, and immune response (Pozhidaeva and Bezsonova, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the protein that guarantees the stability of EZH2 has not been identified until now. USP7 has been reported to stabilize a number of proteins, thereby playing a role in multiple cellular processes (24, 25). Given our finding that USP7 is physically associated with the PRC2 complex, it is reasonable that USP7 would stabilize EZH2 through its deubiquitinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently reported that USP7 promotes breast carcinogenesis by stabilizing PHF8 and upregulating several key cell cycle regulators such as cyclin A2 (24). USP7 was also found to stabilize mediator of DNA damage checkpoint protein 1 (MDC1), which promoted cervical cancer cell survival and conferred cellular resistance to genotoxic insults (25). Although elevated USP7 expression was recently reported as a distinct gene signature of malignant melanoma (26), its specific contribution to melanoma progression is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…53 Moreover, USP7 contributes to cervical carcinogenesis and its expression levels are associated with worse survival rates for patients with cervical cancer. 53 In summary, the findings presented here suggest that USP9X is a novel binding partner of BRCA1 and stabilizes BRCA1. Moreover, knockdown of USP9X enhances the sensitivity of human cancer cells to PARP inhibitor Olaparib and MMS.…”
Section: F I G U R E 3 Usp9x Interacts With Brca1 a And B Hek293tmentioning
confidence: 99%